2015
DOI: 10.1002/dmrr.2636
|View full text |Cite
|
Sign up to set email alerts
|

The brighter (and evolutionarily older) face of the metabolic syndrome: evidence from Trypanosoma cruzi infection in CD‐1 mice

Abstract: Infection with Trypanosoma cruzi, the protozoan parasite that causes Chagas disease, results in chronic infection that leads to cardiomyopathy with increased mortality and morbidity in endemic regions. In a companion study, our group found that a high fat diet protected mice from Trypanosoma cruzi-induced myocardial damage, and significantly reduced post-infection mortality. In the present study, the lethality of T. cruzi (Brazil strain) infection in CD-1 mice was reduced from 55% to 20% by an 8 week pre-feedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 42 publications
4
47
0
2
Order By: Relevance
“…It has been shown that T. cruzi infection causes enlargement of the liver and that the parasites persist in the liver during infection (Sardinha et al 2010; Collier et al 1942). It has also been demonstrated that feeding CD1 mice acutely infected with T. cruzi a HFD increases their survival (Nagajyothi et al 2014; Brima et al 2015). Here we report that although HFD decreases the parasite load in the hearts of acutely infected CD1 mice, it increases the hepatic parasite load compared to the mice fed on RD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that T. cruzi infection causes enlargement of the liver and that the parasites persist in the liver during infection (Sardinha et al 2010; Collier et al 1942). It has also been demonstrated that feeding CD1 mice acutely infected with T. cruzi a HFD increases their survival (Nagajyothi et al 2014; Brima et al 2015). Here we report that although HFD decreases the parasite load in the hearts of acutely infected CD1 mice, it increases the hepatic parasite load compared to the mice fed on RD.…”
Section: Resultsmentioning
confidence: 99%
“…T. cruzi has a high affinity for lipids and lipoproteins, that its rate of invasion depends on host cholesterol levels, and that it alters host lipid metabolism to suit its nutritional requirements, replication and survival (Johndrow et al 2014; Combs et al 2005). We also recently demonstrated that in a murine model of Chagas disease, T. cruzi -infected mice that were fed on a high fat diet (HFD) had increased survival compared to mice fed on a regular diet (RD) (Nagajyothi et al 2014; Brima et al 2015). Adipose tissues of the infected mice play a major role in reducing parasite load and inflammation in HFD fed mice, which may contribute to the increased survival rate during acute T. cruzi infection.…”
Section: Introductionmentioning
confidence: 99%
“…We previously demonstrated that HFD increases the survival rate and decreases the cardiac parasite load during acute infection compared to RD mice [2]. We also reported that the treatment with an anti-diabetes drug metformin decreases mortality both in RD and HFD fed T. cruzi infected mice compared with metformin untreated infected mice during acute infection [5]. In contrast, we found that atorvastatin increases mortality in T. cruzi infected mice during acute infection and treatment with atorvastatin also caused a significant increase in cardiac parasite load and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue lysates were prepared as previously described [2-5]. An aliquot of each sample (40 μg proteins) was subjected to electrophoresis on a 4-15% gradient SDS-PAGE and the proteins transferred to nitrocellulose filters for immunoblot analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation